2001
DOI: 10.1002/1521-4141(2001010)31:10<2970::aid-immu2970>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Direct activation of dendritic cells by the malaria parasite,Plasmodium chabaudi chabaudi

Abstract: A primary infection of mice with Plasmodium chabaudi chabaudi (AS) is characterized by a rapid and marked inflammatory response. Typically, IL‐12, TNF‐α  and IFN‐γ  are produced in the spleen, and are transiently present in plasma. The cells involved in this early response are unknown. Here we show that dendritic cells derived from GM‐CSF‐stimulated mouse bone marrow cultures produce TNF‐α  within 30 min of exposure to P.c.chabaudi schizonts. IL‐6, IL‐12p40 and p70 follow this. The production of these cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
65
3

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 40 publications
2
65
3
Order By: Relevance
“…Both studies showed that when DCs are matured in vitro in the presence of infected E, they express lower levels of class II MHC and costimulatory proteins and provide poorer stimulation for T cells than control DCs. By contrast, our results (13) as well as those of Seixas et al (14) found increased levels of class II MHC and costimulatory proteins on DCs during both P. yoelii infection and interaction with P. chabaudi, although neither study tested the ability of DCs to activate naive T cells.…”
contrasting
confidence: 94%
“…Both studies showed that when DCs are matured in vitro in the presence of infected E, they express lower levels of class II MHC and costimulatory proteins and provide poorer stimulation for T cells than control DCs. By contrast, our results (13) as well as those of Seixas et al (14) found increased levels of class II MHC and costimulatory proteins on DCs during both P. yoelii infection and interaction with P. chabaudi, although neither study tested the ability of DCs to activate naive T cells.…”
contrasting
confidence: 94%
“…In mouse models of malaria, DCs are thought to play an important role in the induction of Th1-dependent immune responses that are protective against bloodstage malaria infection (2,6,9). In the present study, we describe a new flow cytometry technique we developed to measure levels of phagocytosis of pRBCs and nRBCs by mouse BM-derived or spleen DCs in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies using mouse models of malaria have provided evidence for an important role of DCs in inducing protective immunity to blood-stage malaria. Plasmodium chabaudi chabaudi schizonts were found to induce bone marrow (BM)-derived DCs to express MHC class II and costimulatory molecules and to produce IL-12, TNF-␣, and IL-6 (6). In mice infected with P. chabaudi, CD11c ϩ DCs were observed to migrate from the marginal zone of the spleen to the CD4 ϩ T cell-rich periarteriolar lymphoid sheath and to exhibit up-regulated expression of costimulatory molecules as well as increased production of IFN-␥ (7).…”
mentioning
confidence: 99%
“…Antigen-presenting cells (APCs) produce interleukin 12 (IL-12), IL-15, IL-18, and tumor necrosis factor alpha (TNF-␣) (17,26,31,32,37,38,40,44,45,48), which can rapidly activate cells of the innate immune system to produce gamma interferon (IFN-␥) (31,32,44,64). After several days (around 5 days in mice), IFN-␥ from ␣␤ T cells begins to dominate the response.…”
mentioning
confidence: 99%